Evaluating the Effectiveness of Systematic Investment Plans (SIPs) in Enhancing Wealth Among Salaried Professionals (International Journal of Environmental Sciences, 2025)
Systematic Investment Plan (SIP) have emerged as a popular and effective investment strategy for salaried professionals aiming to achieve long-term financial goals. This paper explores the pivotal role of SIP in wealth creation by analysing their benefits, flexibility, and the disciplined investment approach they offer. By enabling regular and small contributions, SIP mitigate the financial burden of lump-sum investments and help individuals harness the power of compounding. The study also delves into the potential of SIP to generate substantial returns while minimising risks through rupee cost averaging. Additionally, this research highlights the psychological and behavioural advantages of SIP, particularly in fostering consistent saving habits among salaried professionals. This paper underscores the critical factors influencing the selection of SIP and alignment with diverse financial goals, making them a robust investment avenue for creating wealth over time.